2022
DOI: 10.1039/d2ta05258j
|View full text |Cite
|
Sign up to set email alerts
|

Penta-OsP2 and penta-Rhs2 sheets derived from marcasite and pyrite with low lattice thermal conductivity

Abstract: Inspired by recent experiment in the synthesis of penta-FeS2 sheet by chemically cleaving bulk iron pyrite via liquid-phase exfoliation, in this work, we theoretically demonstrate that stable penta-OsP2 and penta-RhS2...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…The delocalization of electron and the localization of coherent phonon can be modulated simultaneously to obtain the large electronic conductivity and small thermal conductivity, and then the largest ZT . [ 41 ] The lattice thermal conduction has been considered in the BoltzTrap program [ 35 ] algorithm based on the Boltzmann transport equation (BTE), thus the lattice thermal conductance is considered in recent reported theoretical works [ 42 ] calculated with BoltzTrap program, and in our calculations.…”
Section: Resultsmentioning
confidence: 99%
“…The delocalization of electron and the localization of coherent phonon can be modulated simultaneously to obtain the large electronic conductivity and small thermal conductivity, and then the largest ZT . [ 41 ] The lattice thermal conduction has been considered in the BoltzTrap program [ 35 ] algorithm based on the Boltzmann transport equation (BTE), thus the lattice thermal conductance is considered in recent reported theoretical works [ 42 ] calculated with BoltzTrap program, and in our calculations.…”
Section: Resultsmentioning
confidence: 99%
“…61 The increase of the period length of the superlattice can relatively decrease the mean free path ( L ), which can overcome the shortcoming of L being larger with the decrease of temperature. The lattice thermal conduction has been considered in the BoltzTrap program algorithm based on the Boltzmann transport equation (BTE); thus the lattice thermal conductance is considered in recently reported theoretical studies 9,62 calculated with the BoltzTrap program and in our calculations.…”
Section: Resultsmentioning
confidence: 99%
“…The carrier mobility and photocurrent anisotropy ratios reach 3.9 and 2.3, respectively, with a current switching ratio of about 10 8 and a photoresponsivity of 5.2 × 10 4 AW –1 . The first-principles calculation results have shown that the pentagonal 2D BCN and BNSi structures are highly stable and have significant optical anisotropy in the UV and visible regions with ultrahigh hole mobility and anisotropy ratios. , In addition, other pentagonal 2D structures are predicted to be stable by calculations, such as NiX 2 (X = S, Se, Te), RhS 2 , CNP, and PBN . However, their anisotropy in electronic and optical properties has not been reported.…”
Section: Introductionmentioning
confidence: 99%